Improving the Green Economy Utilizing ReadCharge Solar Literacy Technology at SMP Arrihlah - Nusraningrum, Dewi; Hasibuan, Sawarni; Astuti, Dian Widi; Kusuma, Prima Wijaya; Mahendra, Dendi (Jurnal Abdi Masyarakat (JAM), 2025)
The empowerment of this community partnership implements a program to improve the green economy by increasing reading interest among Arrihlah Islamic Junior High School students by utilizing solar-based ReadCharge technology. The initiative aims to encourage literacy in schools and introduce renewable energy to students as part of sustainable environmental solutions. With the use of environmentally friendly technology, it is hoped that awareness of the importance of green technology in supporting the education and economic development of the community will be created. The program started with designing and building a solar-powered stand-up ReadCharge, then making the design, making the standard operating for its use, providing reading books with a variety of interesting options, and providing training on the use of ReadCharge to students, teachers, parents, and community leaders around Arrihlah Junior High School in several trainings. The training is organized systematically, from the introduction of ReadCharge and its use to its maintenance. The training evaluation provided an overview that ReadCharge delivers an in-depth understanding of the use of solar power to preserve the environment and increase reading interest for students, teachers, and the community. The practical implications of empowering community partnerships funded by grants from the Ministry of Education and Culture are part of the Government's program that encourages people to develop and utilize renewable energy, namely energy sourced from solar heat.